Intervensi Kebersyukuran dan Kesejahteraan Penyandang Disabilitas Fisik - Wahyu Dewanto; Sofia Retnowati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
This study was aimed to examine the effect of gratitude intervention towards people with physical disabilities well-being. The participants were two groups of people with physical disabilities (8 people for experimental group and 5 people for control group). The design of this study was untreated control group design with dependent pre-test and post-test samples. The similar treatment was also given for control group as a waiting list after intervention for experimental group. Well being was assessed using SPANE, PWS, and PTS. The result showed that there are significant differences in wellbeing score between experimental group and control group which are measured by SPANE U test -2,509, p=0,012. PWS U test -2,874, p=0,04. PTS U test -2,590, p=0,010.